Implementing Classroom Management for Grade 4 in IPAS Lessons at Elementary School - Aulia Dita Ramadhani; Ika Ratnaningrum (Postgraduate, University of Mataram, 2025)
This study aims to demonstrate the importance of classroom management skills in creating and maintaining a classroom atmosphere for effective learning. The study used a descriptive qualitative method with eight research subjects consisting of 1 principal, 1 class teacher, and 6 students. Data were collected through observation, interviews, and documentation. The results showed that the implementation of classroom management in 4th grade science learning at SDN Tegalsari 02 Semarang City was carried out in accordance with the teaching module design and predetermined learning outcomes, starting from the introductory, core, and closing activities. Supporting factors for the effectiveness of classroom management implementation consisted of 1) principal support, 2) teacher training, 3) teacher performance evaluation, and 4) collaboration between schools, teachers, and parents. Meanwhile, inhibiting factors consisted of 1) low teacher motivation, 2) teachers having difficulty adapting to the curriculum, 3) limited learning media, 4) conventional learning methods, 5) disruptive student behavior, and 6) classroom conditions. The solutions found to overcome these obstacles are 1) the application of rewards and punishments, 2) the application of a variety of learning methods, 3) outing classes, 4) evaluation of school learning communities, and 5) In-House Training.